Evaluation of Biochemical and Pathological Parameters at Different Doses of Cisplatin in Experimental Animal Model: Toxicological Study on an Antineoplastic Drug - Sultana, Farhana; Islam, Muhammed Mohibul; Amin, Mohammad Nurul; Jahan, Nusrat; Kabir, Asma; Emran, Talha Bin; Sutradhar, Bibek Chandra; Banik, Sujan (UI Scholars Hub, 2022)
Background: This study aimed to assess the effect of cisplatin-induced toxicities on biochemical and pathological parameters such as body, liver, and kidney weights, blood urea nitrogen (BUN), creatinine, alanine aminotransferase (ALT), and blood cells (RBCs and WBCs) in white Swiss albino mice. Methods: Cisplatin’s potential toxic effects on body, liver, and kidney weights were evaluated using standard laboratory methods. Blood biochemical levels such as BUN, creatinine, and ALT levels were determined by an auto-hemolyzer using commercial diagnostic kits. Blood cells (RBCs and WBCs) were counted under a microscope by a hemocytometer. Results: Cisplatin’s potential toxic effects on body, liver, and kidney weights were evaluated using standard laboratory methods. Blood biochemical levels such as BUN, creatinine, and ALT levels were determined by an auto-hemolyzer using commercial diagnostic kits. Blood cells (RBCs and WBCs) were counted under a microscope by a hemocytometer. Conclusions: This study suggested to increase caution when using cisplatin, particularly at high doses. Further investigation shall be performed to minimize its toxic effect and optimize its use.